(1+tana)(1+sin2a+cos2a)-3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 06:27:46
(1+tana)(1+sin2a+cos2a)-3(1+tana)(1+sin2a+cos2a)-3(1+tana)(1+sin2a+cos2a)-3(1+tana)(1+sin2a+cos2a)-3
(1+tana)(1+sin2a+cos2a)-3
(1+tana)(1+sin2a+cos2a)-3
(1+tana)(1+sin2a+cos2a)-3
(1+tana)(1+sin2a+cos2a)-3
=[(cosa+sina)/cosa][2cosa(cosa+sina)]-3
=2(sina+cosa)^2-3
=2sin2a-1
(1+tana)(1+sin2a+cos2a)-3
=[(cosa+sina)/cosa]*[2cosa(sina+cosa)]-3
=2sin2a-1
(1+tana)(1+sin2a+cos2a)-3=(1+tana)(2cosaxcosa+2sinacosa)-3=(1+sina/cosa)(sina+cosa)2cosa-3=2(sina+cosa)(sina+cosa)-3
(1+tanα)(1+sin2α+cos2α)-3=[(cosα+sinα)/cosα](sin2α+2cosα^2)-3=2(sinα+cosα)^2-3=2sin2α-1
证明1+sin2a/2cos^2a+sin2a=1/2tana+1/2
(1+sin2A)/(2cos的平方+sin2A)==0.5tanA+0.5
试证:1+sin2a/cos^2-sin^2=1+tana/1-tana
求证cos^2A/1/tanA/2 -tanA/2 =1/4sin2A
化简sin2a(1+tana*tana/2)
已知tana=1/3,则cos^2a+1/2sin2a的值是
已知tana=1/3,求cos^a+1/2sin2a的值
已知tana=1/2,则cos2a+sin2a+1/cos^a=
已知tana=1/2,则sin2a+cos²a等于
已知tana=2,则(sin2a-cos2a)/(1+cos^2a)=
(1+sin2a)/(cos平方a-sin平方a)=-3,求tana的值
若tana=2,则(sin2a-cos^2a)/(1+cos2a)=_____求步骤
已知tana=2,求[sin2a+cos^2(π-a)]/(1+cos2a)的值
已知tana=2,求【sin2a+cos^2(π-a)】/(1+cos2a)的值
已知tana=1/3,则sin2a+cos平方a=
已知cos(π/4+a)=4/5,求(sin2a-2sin^2a)(1-tana)
tana=-1/3 (2sin^a+sin2a)/cos(a-π/4)=?-π/2
求证:cos²a/(cota/2)-(tana/2)=1/4sin2a